The imperial rationality within BioTrade: A contribution to the neoextractivist debate (Alternautas, 2022)
This article addresses a recent debate on neoextractivism in Latin America by presenting ethnographic research on BioTrade in Peru. While biodiversity conservation is usually not associated with extractivist projects, such as open-pit mining or industrial monocultures, the case study on Sacha Inchi presented here reveals the same basic patterns of resource extraction: a logic that places the requirements of global markets over local realities; that chooses the needs of exporting firms over the concerns of the rural populations; and that favors the perspective of the capital over that of its hinterland. The findings lead the author to interpret BioTrade, in this case, as a form of neoextractivism. It claims to pursue goals of social equity and environmental sustainability, while in practice adopting the same imperial rationality as the century-old extractivist project, characteristic for Latin America. Thus, this article contributes to the debate by reminding of the social, or “cultural”, preconditions for (neo)extractivism, namely the “coloniality of power” (Quijano, 1992), and thus the construction, subordination, and exploitation of the Other. In a post-structural reading it suggests that, in the contemporary arena of sustainable development, the neoliberal rationality constitutes a mechanism that reproduces colonial lines of social differentiation by creating difference along the lines of the ability to live up to its emblematic figure of the entrepreneur.